Ask Question
31 March, 21:43

If f (X) = 2x-4 and g (X) = x^2 - 4x solve f (3) - 1

+3
Answers (1)
  1. 31 March, 23:29
    0
    1

    Step-by-step explanation:

    f (3) = 2*3 - 4 ➡2

    f (3) - 1 = 1
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “If f (X) = 2x-4 and g (X) = x^2 - 4x solve f (3) - 1 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers